Effects of television viewing on brain structures and risk of dementia in the elderly: Longitudinal analyses - Takeuchi, Hikaru; Kawashima, Ryuta (Frontiers in Neuroscience, 2023)
Longer TV viewing in the elderly and in children is associated with subsequent greater decline of various cognitive functions including verbal working memory, but results of its association with subsequent risk of dementia were divided. In this longitudinal cohort study of UK biobank, we showed after corrections of a wide range of potential confounders, longer TV viewing was associated with increased risk of subsequent onset of dementia, as well as subsequent greater decline in intracellular volume fraction (ICVF) in the extensive areas of right lateral temporal cortex and the right medial temporal cortex, in the area around the left middle and inferior temporal cortex as well as the left fusiform gyrus, and the area adjacent to the left inferior frontal gyrus, and left insula. These results may suggest prolonged TV viewing was associated with decline in density of neurites (axon, dendrites) in areas particularly implicated in language, communication, and memory, which are altered in dementia.